Prospective Study of Antibiotic Prophylaxis for Prostate Biopsy Involving >1100 Men - Rustom P. Manecksha; Gregory J. Nason; Ivor M. Cullen; Jérôme P. Fennell; Elizabeth McEvoy; Ted McDermott; Robert J. Flynn; Ronald Grainger; John A. Thornhill (The Scientific World Journal)
We aimed to compare infection rates for two 3-day antibiotic prophylaxis regimens for transrectal ultrasound-guided prostate biopsy (TRUSgbp) and demonstrate local microbiological trends. In 2008, 558 men and, in 2009, 625 men had TRUSgpb. Regimen 1 (2008) comprised 400 mg Ofloxacin immediately before biopsy and 200 mg 12-hourly for 3 days. Regimen 2 (2009) comprised Ofloxacin 200 mg 12-hourly for 3 days commencing 24 hours before biopsy. 20/558 (3.6%) men had febrile episodes with regimen 1 and 10/625 (1.6%) men with regimen 2 (𝑃=0.03). E. coli was the most frequently isolated organism. Overall, 7/13 (54%) of positive urine cultures were quinolone resistant and (5/13) 40% were multidrug resistant. Overall, 5/9 (56%) patients with septicaemia were quinolone resistant. All patients were sensitive to Meropenem. There was 1 (0.2%) death with regimen 1. Commencing Ofloxacin 24 hours before TRUSgpb reduced the incidence of febrile episodes significantly. We observed the emergence of quinolone and multidrug-resistant E. coli. Meropenem should be considered for unresolving sepsis.